Impact of hypertension on clinical outcome in patients treated with vascular endothelial growth factor inhibitors. (14th October 2021) - Moriyama, S; Hieda, M; Fukuda, H; Kawano, S; Yokoyama, T; Fukata, M; Kusaba, H; Maruyama, T; Baba, E; Akashi, K
Abstract: Background: Vascular endothelial growth factor (VEGF) family is overexpressed in the tumor microenvironment and induces tumor angiogenesis.1 VEGF signaling pathway (VSP) inhibitors are essential therapeutic drugs for solid cancer patients.2 However, VSP inhibitors often provoke drug-specific anti-angiogenesis in normal tissues, which was referred to as on-target toxicity.2 Hypertension (HTN) is one of the most frequent adverse events caused by VSP inhibitors. A previous report demonstrated that VSP inhibitor-induced hypertension is a favorable prognostic factor, contrarily.3However, multiple VSP inhibitors are administered in various cancer types, and then the relation between VSP inhibitor-associated hypertension and clinical outcome is still controversial. Purpose: The aim of this study is to elucidate the impacts of HTN and the timing of onset on clinical outcome during cancer therapy with VSP inhibitors. Method: We reviewed 2, 348 patients who were treated with VSP inhibitors from the LIFE Study database, consisting of 14 municipality-level information from claims data between 2016 and 2020. According to the timing of HTN onset mode, the patients were stratified into 3 groups; (1) new-onset HTN group (n=334): de novo development after VSP inhibitor administration, (2) pre-existing HTN group (n=1, 363): existing HTN at baseline, including aggravation after VSP inhibitor initiation, and (3) no HTN group (n=651) (Figure 1). The time to treatment failure (TTF) was applied as a surrogate clinical indicator of overall survival. Event-free survival analysis with the log-rank test was conducted for time to first treatment failure amongst the 3 groups. In addition, Cox proportional hazard models adjusted with clinical characteristics were performed to investigate independent factors for TTF. Results: In the event-free survival analysis, both the new-onset HTN and the pre-existing HTN were associated with prolongation of TTF, compared to the non-HTN (p<0.001 and p<0.001, respectively, by Bonferroni correction) (Figure 2). The New-onset HTN was significantly associated with longer TTF than pre-existing HTN (p<0.001). In Cox proportional hazard model adjusted with age, sex, past medical history, primary cancer lesion, and type of VSP inhibitors, the new-onset HTN and the pre-existing HTN were independent favorable factors, compared to the non-HTN [new-onset HTN: Hazard ratio (HR) 0.62, 95% confidence interval (CI) 0.54 - 0.71, p<0.001; and pre-existing HTN: HR 0.85, 95% CI 0.77 - 0.94, p<0.005]. Moreover, the New-onset HTN was also a significant factor for longer TTF, compared to the pre-existing HTN [HR 0.72, 95% CI 0.64 - 0.82, p<0.001]. Conclusion: In patients treated with VSP inhibitors, both new-onset and pre-existing HTN are independent factors for a favorable clinical outcome, especially new-onset HTN after VSP inhibitors administration. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Japan Society for the Promotion of Science (JSPS) Grants-in-Aid for Scientific Research (KAKENHI)